Peran Orang Tua dalam Pendidikan Islam Pada Anak Usia Dini - Adelfa Yuriansa; Karuni Humairah Arta; Ummi Habibatul Islamiyah (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2023)
The foremost and primary education in Islam is the Islamic education of children within the family. Islamic education is provided from an early age to instill a sense of belief, faith, and Islam in the child. The presence of Islamic education from an early age demonstrates the consistency of parents and children in determining the future and the child's environment in an Islamic manner. The role of parents in early childhood, according to Islam, is crucial in the development and formation of character during the child's golden age. During this golden age, children will mimic what their parents do. Therefore, parents must pay attention to providing good education for their children. Data collection in this research is conducted by gathering literature, reading, taking notes, and processing research materials. The research approach is analyzed using qualitative descriptive analysis. This study aims to explain the characteristics of Islamic education for early childhood from the perspective of Islamic education, thus building a solid foundation for early childhood development. Abstrak Pendidikan yang paling pertama dan utama dalam islam adalah pendidikan islam anak dalam keluarga. Pendidikan islam diberikan pada saat usia dini untuk menumbuhkan rasa keprcayaan, iman dan islam pada anak. Dengan adanya pendidikan islam sejak usia dini menunjukkan konsistensi orang tua dan anak untuk menentukan masa depan dan lingkungan anak secara islam. Peran orang tua pada anak usia dini dalam pandangan islam sangat penting dalam perkembangan dan pembentukan karakter di masa emas anak. Pada masa emas anak akan meniru apa yang dilakukan orang tua. Oleh karena itu, orang tua harus memperhatikan dalam memberikan pendidikan yang baik untuk anak. Pengumpulan data dalam penelitian ini dilakukan dengan mengumpulkan data pustaka, membaca, mencatat, dan mengolah bahan penelitian. Pendekatan penelitian dianalisis dengan menggunakan analisis deskriptif kualitatif. Penelitian ini bertujuan menjelaskan karakteristik pendidikan islam bagi anak usia dini yang ditinjau dalam perspektif pendidikan islam sehingga membangun kemampuan dasar yang baik bagi anak usia dini.